2016
DOI: 10.1002/anie.201607960
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Dehydrogenation of Methane by [ReN]+

Abstract: The thermal reaction of the diatomic rhenium nitride cation [ReN] with methane has been explored using FT-ICR mass spectrometry complemented by high-level quantum chemical calculations. Mechanistic aspects of the reaction have been addressed to uncover scenarios for the competitive generation of a methylene and a hydrogen cyanide ligand attached to the rhenium center. The role the nitrogen atom plays in the reactive [ReN] /CH couple is elucidated, and the cause of the rather different reactivities of [ReN] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 46 publications
1
30
0
1
Order By: Relevance
“…It has been experimentally identified that the bare Au 1–4 + clusters can activate methane through oxidative addition of the C−H bond onto single gold atoms (Au δ+ +CH 4 →HAuCH 3 ), even though the energies of the relevant transition states were generally located above those of the reactants and the intermediates with the [HAuCH 3 ] moiety were thermodynamically very unstable . A lot of effort has been devoted to uncovering the ligand effect on the reactivity of cationic gold by preparation of gold oxide as well as carbide cations and gold‐doped heteronuclear oxide clusters . Completely different mechanisms of gold‐mediated C−H activation have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…It has been experimentally identified that the bare Au 1–4 + clusters can activate methane through oxidative addition of the C−H bond onto single gold atoms (Au δ+ +CH 4 →HAuCH 3 ), even though the energies of the relevant transition states were generally located above those of the reactants and the intermediates with the [HAuCH 3 ] moiety were thermodynamically very unstable . A lot of effort has been devoted to uncovering the ligand effect on the reactivity of cationic gold by preparation of gold oxide as well as carbide cations and gold‐doped heteronuclear oxide clusters . Completely different mechanisms of gold‐mediated C−H activation have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…In ad ifferent context, gas-phase CÀNc oupling of NH 3 with methane has served as an instructive model for the largescale DEGUSSA (BMA) [15] and Andrussow [16] processes.F or example,the atomic transition-metal cations M + (M = Rh, W, Os,I r, Pt) [17] as well as diatomic [PtM] + (M = Cu, Ag, Au) [18] consecutively activate methane and ammonia to afford CÀN coupling.A ctivation of methane by [TaN] + generates [Ta-(NCH 2 )] + , [19] while competitive generation of [NRe(CH 2 )] + and [HRe(NCH)] + was observed for the [ReN] + /CH 4 couple. [20] In addition, an unprecedented alkyne/nitrile gasphase metathesis takes place when the ligated nitrido dication complex [LFeN] 2+ (L = 2,6-bis(2-methyl-1,3-diaminopropan-2-yl)pyridine) is reacted with alkynes to form RCN and [LFe(CR)] + . [21] Herein, we report an ovel example in which triatomic [CeON] + selectively delivers its nitrogen atom to methane at ambient temperature;t his reactivity contrasts sharply with that of [CeO 2 ] + ,w hich is thermally inert towards this substrate.M echanistic aspects of the reaction of the [CeON] + /CH 4 couple will be revealed, and the associated electronic origins discussed.…”
mentioning
confidence: 99%
“…[16] Hierbei aktivieren die atomaren Übergangsmetallkationen M + (M = Rh, W, Os,I r, Pt) [17] sowie die diatomaren Cluster [PtM] + (M = Cu, Ag, Au) [18] Methan und Ammoniak konsekutiv unter C-N-Bindungsknüpfung.F erner bildet [TaN] + unter Methanaktivierung [Ta(NCH 2 )] + , [19] während fürdas Reaktionspaar [ReN] + /CH 4 die kompetitive Erzeugung von [NRe(CH 2 )] + und [HRe-(NCH)] + beobachtet wurde. [20] Eine zuvor nicht beobachtete Alkin/Nitril-Metathese findet darüber hinaus in der Gasphasenreaktion des zweifach geladenen Nitridokomplexes …”
unclassified